Basic atomic interactions of accelerated heavy ions in matter : atomic interactions of heavy ions /: atomic interactions of heavy ions. (2018) - Tolstikhina, Inga; Imai, Makoto; Winckler, Nicolas; Shevelʹko, V. P (Vi︠a︡cheslav Petrovich)
No abstract available